2018
DOI: 10.1016/j.bbrc.2017.11.073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface charge on the thermal stability and ice recrystallization inhibition activity of antifreeze protein III (AFP III)

Abstract: The aim of this study was to examine the effect of chemical cationization on the structure and function of antifreeze protein III (AFP III) over an extreme temperature range (-40°C to +90°C) using far-UV synchrotron radiation circular dichroism (SRCD) and ice recrystallization inhibition (IRI) assays. Chemical cationization was able to produce a modified AFP III with a net cationic charge at physiological pH that had enhanced resistance to denaturation at elevated temperatures, with no immediate negative impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This also shows that designing a multivalent AFP is non-trivial, with the correct chemistry being essential. Previous studies suggest excess charge does not affect AFP activity and was ruled out as the cause 36. In contrast, the covalent hybrid nanoparticle SNAP-AFP-BG-pHEA 45 @Au 4 was found to be a very potent IRI, Fig.…”
mentioning
confidence: 79%
“…This also shows that designing a multivalent AFP is non-trivial, with the correct chemistry being essential. Previous studies suggest excess charge does not affect AFP activity and was ruled out as the cause 36. In contrast, the covalent hybrid nanoparticle SNAP-AFP-BG-pHEA 45 @Au 4 was found to be a very potent IRI, Fig.…”
mentioning
confidence: 79%
“…The pH was monitored constantly and adjusted to 6.0–6.5 as required for the first 6 h. The mixture was left stirring at room temperature overnight (∼18 h). 37 Finally, the solution was filtered through a 0.22 μm syringe filter to remove any precipitates, dialysed against dH 2 O for 24 h and concentrated following the same procedure described before.…”
Section: Methodsmentioning
confidence: 99%
“…[54] Proteins other than collagen have also been studied by meanso fU Vand IR spectroscopy, notably taking advantage of the high flux of synchrotron radiation to reach good signal-tonoise ratios for far-UV-CD studies. Heat-induced denaturation of matrix proteins [55] and antifreeze protein III [56] has been observed, but this process also occursu pon sufficient exposure to UV light. By controlling synchrotron radiation, CD-UVd enaturationc an even provide information about protein stability and receptor-ligand bindingi nteractions, particularly if thermal studies are inconclusive.F or instance,i th as been shown that gold nanoparticles or ligandss tabilize humans erum albumin upon irradiation over the wavelength range of 185-250 nm.…”
Section: Irradiation By Nonionizing Radiationmentioning
confidence: 99%